2018
DOI: 10.1002/pits.22176
|View full text |Cite
|
Sign up to set email alerts
|

What are urban teachers thinking and feeling?

Abstract: Teachers in urban schools experience significant stressors that can impact their effectiveness, well-being, retention, and ability to meet the needs of their students. The current mixed methods study explored 160 urban teachers' thoughts and feelings in response to challenging classroom situations, factors that predicted the prevalence of these reactions, and teachers' help-seeking attitudes. Results revealed the most prevalent thoughts that emerged were inability to resolve the situation, problem-solving, fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…Because of the combination, simple linear regressions were calculated to predict depression and stress. The results of the model were significant, F (1,170) 5 61.62, p < 0.001, R 2 To investigate how well Strength predicts anxiety when controlling for class level, hierarchical multiple regression was used to control the confounding factor. When the class level was entered alone, it significantly predicted anxiety, F (1,170) 5 5.21, p 5 0.02, adjusted R 2 5 0.02 (only 2% of the variance in anxiety could be predicted by class level).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the combination, simple linear regressions were calculated to predict depression and stress. The results of the model were significant, F (1,170) 5 61.62, p < 0.001, R 2 To investigate how well Strength predicts anxiety when controlling for class level, hierarchical multiple regression was used to control the confounding factor. When the class level was entered alone, it significantly predicted anxiety, F (1,170) 5 5.21, p 5 0.02, adjusted R 2 5 0.02 (only 2% of the variance in anxiety could be predicted by class level).…”
Section: Resultsmentioning
confidence: 99%
“…Teachers worldwide demonstrate susceptibility to mental health issues such as depression, anxiety and stress based on the multitude of primary stressors they encounter, including a lack of resources, a pressure to fulfill multiple roles, interpersonal troubles, demanding working conditions, low student achievement and excessive workload [1][2][3][4][5]. Further, numerous studies have demonstrated that these primary stressors threaten the psychological wellbeing of teachers internationally [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Data analyzed in this study were part of a larger study on the social and emotional experiences of urban teachers (Camacho & Parham, 2019; Camacho et al, 2018). Study methods were approved by the first author's Institutional Review Board, and informed consent was obtained from all participants.…”
Section: Methodsmentioning
confidence: 99%
“…In this manner, researchers utilized both concept‐driven and data‐driven categories in the construction of their coding framework (Schreier, 2014). Qualitative data pertaining to teachers' cognitive responses were analyzed in a previous study using a data‐driven approach to present novel findings about the content of urban teachers' thoughts in reaction to situational challenges (Camacho et al, 2018). In the present study, these data were re‐analyzed using a distinct approach to investigate a substantively different topic, that is, their role in teacher burnout.…”
Section: Methodsmentioning
confidence: 99%
“…"Teacher stress" was first specifically described by Kyriacou [3] as "a response syndrome of negative effects (such as anger or depression) resulting from the general teacher's job". Teachers' experiences of stress at work have received extensive coverage in the literature [4][5][6][7][8], with stress sources recently summarized as the following: (1) teaching unmotivated students, (2) maintaining discipline, (3) time pressures and workload, (4) coping with change, (5) being evaluated by others, (6) dealings with colleagues, (7) self-esteem and status, (8) administration and management, (9) role conflict and ambiguity, and (10) poor working conditions [9]. Some of these sources reflect contextual factors that are intrinsic to the job and shape the method of teaching (eg, classroom setting, timetabling, and instructing), which have also been referred to as the school climate [10,11].…”
Section: Introductionmentioning
confidence: 99%